Penggunaan Puzzle sebagai Solusi Peningkatan Motivasi Belajar Siswa Kelas VI di SD Negeri 03 Sengare - Didik Prihantoro (Perkumpulan Kualitama Edukatika Indonesia, 2022)
This study aims to describe puzzle media as a solution to increase student motivation for elementary/MI students. In this study using library research, is research carried out in data collection, then in solving a problem a research uses library sources. The data contained in library sources consist of research journals, books relevant to research, dictionaries, magazines, encyclopedias, documents, sources from the internet and others. The technique used in this research is documentation technique. In analyzing the data that has been collected using content analysis techniques. Media is an intermediary or introduction. Puzzle media is able to foster student motivation to keep trying to solve problems, and it is fun for students because it can be repeated. Challenges in puzzle games will give you an addictive effect to keep trying and keep trying until they succeed.